Could Altered Red Cell Indices Reflect Oxidative Stress in Pediatric Atopic Dermatitis? - Gençoğlu, Şule (The European Research Journal, 2026)
Objectives: To investigate whether alterations in red blood cell indices - particularly mean corpuscular volume (MCV), red cell distribution width-coefficient of variation (RDW-CV), mean corpuscular hemoglobin (MCH), and mean corpuscular hemoglobin concentration (MCHC) - reflect systemic oxidative stress and metabolic disturbances in pediatric patients with atopic dermatitis (AD). Methods: A retrospective, cross-sectional study was conducted involving 250 pediatric patients diagnosed with AD and 163 healthy controls. Hematological and biochemical parameters were obtained from hospital records, including complete blood count variables and serum levels of urea, creatinine, AST, ALT, uric acid, TSH, free T4, and vitamin B12. Data were analyzed using distribution assessments, intergroup comparisons, and Spearman correlation tests. Results: Pediatric AD patients exhibited significant alterations in red cell indices. RDW-CV was markedly elevated and showed extreme positive skewness, indicating anisocytosis and disrupted erythropoiesis. RDW-CV strongly correlated with AST and ALT levels. Additionally, MCH positively correlated with vitamin B12 and TSH, while MCHC showed an inverse correlation with ALT. Conclusions: Altered red blood cell indices, especially RDW-CV and MCH, may serve as accessible and cost-effective surrogate markers for systemic oxidative and metabolic stress in pediatric atopic dermatitis. These hematologic parameters could be integrated into routine assessments to support individualized treatment approaches and endotype-specific care strategies in pediatric populations.